2007
DOI: 10.1002/qj.139
|View full text |Cite
|
Sign up to set email alerts
|

Application of a potential vorticity modification method to a case of rapid cyclogenesis over the Atlantic Ocean

Abstract: A method to modify the potential vorticity of a numerical weather analysis is applied to a case of rapid cyclogenesis over the Atlantic Ocean. The development of the cyclone's intensity in terms of mean sea level pressure is underestimated by the Dutch version of the limited-area weather prediction model HIRLAM. The analysis shows a rather clear mismatch between the potential vorticity of the analysis and the corresponding water vapour satellite image. A barotropic displacement of potential vorticity, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Demirtas and Thorpe, 1999;Hello and Arbogast, 2004;Guerin et al, 2006;Kristjánsson, 2006, 2008;Manders et al, 2007) have shown that initial conditions corrected by PV modifications according to WV imagery may lead to substantial reduction of the forecast errors. In these earlier investigations, the authors placed special emphasis on deep North Atlantic cyclones that were poorly forecast by operational meteorological centres.…”
Section: Introductionmentioning
confidence: 99%
“…Demirtas and Thorpe, 1999;Hello and Arbogast, 2004;Guerin et al, 2006;Kristjánsson, 2006, 2008;Manders et al, 2007) have shown that initial conditions corrected by PV modifications according to WV imagery may lead to substantial reduction of the forecast errors. In these earlier investigations, the authors placed special emphasis on deep North Atlantic cyclones that were poorly forecast by operational meteorological centres.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies that focus on modifying the PV field according to WV imagery show its positive effect on reducing forecast error (e.g. Dermitas and Thorpe, 1999;Hello and Arbogast, 2004;Gue´rin et al, 2006;Kristja´nson, 2006, 2008;Manders et al, 2007;Argence et al, 2009). This paper evaluates the forecast results obtained using the PV-WV technique when applied to two different Mediterranean high-impact weather (HIW) events.…”
Section: P U B L I S H E D B Y T H E I N T E R N a T I O N A L M E T mentioning
confidence: 99%
“…Modification of the potential vorticity is a common way to perturb the atmospheric fields. Manders et al (2007) used this method to modify numerical weather forecasts to assess numerical errors within forecasts.…”
Section: Introductionmentioning
confidence: 99%